A quality systems study of Foremost Farms Incorporated - Dela Cruz, Alfredo Jojo G. (College of Engineering, 1996)
The company under study is Foremost Farms, Incorporated, a semi-integrated feedmill and farm, whose main produce is feedmixes for both piggery and poultry farms. The system under study is the production system of one of its two feedmills. It focuses on the production and quality control sections; how the process works, how quality is applied to the system (process organization, management policies). The study was conducted for the purpose of documenting a traditional industry, and evaluating as to how quality improves the system. It first starts off with a systems audit, identifying the major areas for possible improvement. From this, it identifies lack of statistical control at possible points for garnering improvement. From the survey it goes on to manufacturing process, where the process proper is documented, including the quality system affecting it, the standards or specifications for each quality index inspected, as well as the rate of inspection for each such material. It also takes into account the means of coordination of quality work; the quality policies, objectives and general system in use, as well as the people engaged in quality work within the organization. Quality information systems are also present; what quality measures are important, what programs are present, the costs for doing or not doing quality work. Based on the documentation gathered, two major and two minor possible improvement areas are gathered. The two major ones are the lack of sufficient data for process control and the lack of systems and procedures for documenting and analyzing control data. The two minor ones are with regard to the lack of homogeneity in the mixing operation of the feedmill and the possibility of increased inspection.